2017
DOI: 10.1016/j.jvs.2016.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor and vascular endothelial growth factor play a critical role in endotheliogenesis from human adipose-derived stem cells

Abstract: These results indicate that FGF and VEGF are ASC promoters for proliferation, migration, attachment, and endothelial differentiation. FGF and VEGF have a costimulatory effect on ASC endotheliogenesis. These results further suggest that ASCs with enhanced FGF signaling may potentially be used for tissue engineering and cell-based therapies in patients with critical limb ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 39 publications
4
43
0
1
Order By: Relevance
“…Our research emphasis was that the underlying role of VEGF‐Ang‐1‐PLA nano‐sustained release microspheres on ADSC proliferation and differentiation toward ECs. It was reported that pre‐culture in endothelial growth medium enhanced the angiogenic properties of ADSCs (Souza et al, ), and Sophia Khan found that the two vital angiogenesis factors FGF and VEGF played critical roles in endotheliogenesis from human ADSCs (Khan et al, ). The present study VEGF‐Ang‐1‐PLA microspheres facilitated HGF secretion to promote ADSC proliferation and enhance CD31 + cells, but scarcely influenced the expression levels of VEGF and Ang‐1.…”
Section: Discussionmentioning
confidence: 99%
“…Our research emphasis was that the underlying role of VEGF‐Ang‐1‐PLA nano‐sustained release microspheres on ADSC proliferation and differentiation toward ECs. It was reported that pre‐culture in endothelial growth medium enhanced the angiogenic properties of ADSCs (Souza et al, ), and Sophia Khan found that the two vital angiogenesis factors FGF and VEGF played critical roles in endotheliogenesis from human ADSCs (Khan et al, ). The present study VEGF‐Ang‐1‐PLA microspheres facilitated HGF secretion to promote ADSC proliferation and enhance CD31 + cells, but scarcely influenced the expression levels of VEGF and Ang‐1.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelial differentiation of ASCs was induced using EGM2, as commonly performed . This media is supplemented with factors implicated in the differentiation and survival of ECs, including vascular endothelial growth factor and basic fibroblast growth factor .…”
Section: Resultsmentioning
confidence: 99%
“…The failure of previous investigations to detect the limited endothelial plasticity of ASCs may be largely attributed to their use of qualitative assays and their omission of representative primary cell controls in evaluating an endothelial phenotype. The expression of endothelial genes by ASCs has often been evaluated by end‐point PCR , and that of proteins by Western blots , immunofluorescence microscopy , and flow cytometry . Similarly, AcLDL uptake has predominantly been assessed by immunofluorescence microscopy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…* Table includes data from the following references [2,18,26,27,28,29,30,31,32,33,34,35,36]. Abbreviations: CXCL12, C-X-C motif chemokine ligand 12; EGF, endothelial growth factor; FGF, fibroblast growth factor; IL-10, interleukin-10; M-CSF, monocyte colony-stimulating factor; NO, nitric oxide; PDGF, platelet derived growth factor; TNF-α, tumor necrosis factor-α; VEGF, vascular endothelial growth factor.…”
Section: Tablementioning
confidence: 99%